Changes in body weight in response to pecan-enriched diets with and without substitution instructions: a randomised, controlled trial - Liana L. Guarneiri; Chad M. Paton; Jamie A. Cooper (Journal of Nutritional Science, 2022)
Substantial evidence suggests that regular tree nut consumption does not lead to changes in body weight (BW). However, these studies used a variety of dietary substitution instructions which may confound the interpretation of prior BW outcomes. The purpose of the present study was to examine the impact of daily pecan consumption, with or without isocaloric substitution instructions, on BW and composition. This was an 8-week randomised, controlled trial with three treatments: a nut-free control group (n 32) and two pecan groups. ADD (n 30) consumed pecans (68 g/d) as part of a free-living diet, and SUB (n 31) substituted the pecans (68 g/d) for isocaloric foods from their habitual diet. BW and total body fat percentage (BF) were measured, and theoretical changes in these outcomes if pecans were consumed without compensation were determined. BW increased in all groups across the intervention, and there was a trend (P = 0⋅09) for an increase in ADD (1⋅1 ± 0⋅2 kg) and SUB (0⋅9 ± 0⋅3 kg) compared to control (0⋅3 ± 0⋅2 kg). In addition, there was increased BF in SUB (1⋅0 ± 0⋅3 %; P = 0⋅005) but not ADD (0⋅1 ± 0⋅2 %) or control (−0⋅2 ± 0⋅3 %) There was a large difference in the actual v. theoretical change in BW regardless of pecan treatment (actual: 1⋅1 ± 0⋅2 and 0⋅9 ± 0⋅3 v. theoretical: 3⋅3 ± 0⋅0 and 3⋅2 ± 0⋅0 kg in ADD and SUB, respectively; P < 0⋅001). Furthermore, there was a difference in actual v. theoretical change in BF in ADD (0⋅1 ± 0⋅2 v. 1⋅2 ± 0⋅1 %; P = 0⋅002) but not SUB or control. In conclusion, daily pecan consumption for 8 weeks did not result in significant weight gain, regardless of dietary substitution instructions.